2006
DOI: 10.1128/aem.72.3.2014-2021.2006
|View full text |Cite
|
Sign up to set email alerts
|

CandidatusThiobios zoothamnicoli,” an Ectosymbiotic Bacterium Covering the Giant Marine CiliateZoothamnium niveum

Abstract: Zoothamnium niveum is a giant, colonial marine ciliate from sulfide-rich habitats obligatorily covered with chemoautotrophic, sulfide-oxidizing bacteria which appear as coccoid rods and rods with a series of intermediate shapes. Comparative 16S rRNA gene sequence analysis and fluorescence in situ hybridization showed that the ectosymbiont of Z. niveum belongs to only one pleomorphic phylotype. The Z. niveum ectosymbiont is only moderately related to previously identified groups of thiotrophic symbionts within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 46 publications
6
104
0
Order By: Relevance
“…This view of the Z. niveum niche on the peat banks of Belizean barrier islands resembles the conditions in locations on Corsica, France, where it recently has been found. Here it lives attached to rock surfaces in the vicinity of decaying sea grass (Rinke et al 2007). Micro-molar concentration of sulWde in norm-oxic seawater is also the medium in which Z. niveum has been successfully cultivated.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This view of the Z. niveum niche on the peat banks of Belizean barrier islands resembles the conditions in locations on Corsica, France, where it recently has been found. Here it lives attached to rock surfaces in the vicinity of decaying sea grass (Rinke et al 2007). Micro-molar concentration of sulWde in norm-oxic seawater is also the medium in which Z. niveum has been successfully cultivated.…”
Section: Discussionmentioning
confidence: 99%
“…The sulWde concentration of 3 mol sulWde L ¡1 is where Rinke et al (2007) found optimal growth. This external concentration is well within the range measured between the colonies in situ by Vopel et al (2005).…”
Section: ¡1mentioning
confidence: 99%
See 3 more Smart Citations